2017
DOI: 10.1002/hbm.23566
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical mechanisms of brain‐machine interfaces

Abstract: Technical advances in the field of Brain-Machine Interfaces (BMIs) enable users to control a variety of external devices such as robotic arms, wheelchairs, virtual entities and communication systems through the decoding of brain signals in real time. Most BMI systems sample activity from restricted brain regions, typically the motor and premotor cortex, with limited spatial resolution. Despite the growing number of applications, the cortical and subcortical systems involved in BMI control are currently unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 94 publications
(104 reference statements)
4
33
0
Order By: Relevance
“…The SMA has been shown to play a role in SCP and motor imagery BCIs in humans and in studies with monkeys controlling a neuronal interface (Carmena et al, ; Halder et al, ; Hinterberger et al, ; Marchesotti et al, ). Interestingly, neural activation in the SMA has been found to be correlated with performance in auditory attention tasks, similar to the previous findings relating to motor imagery BCI performance (Seydell‐Greenwald, Greenberg, & Rauschecker, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMA has been shown to play a role in SCP and motor imagery BCIs in humans and in studies with monkeys controlling a neuronal interface (Carmena et al, ; Halder et al, ; Hinterberger et al, ; Marchesotti et al, ). Interestingly, neural activation in the SMA has been found to be correlated with performance in auditory attention tasks, similar to the previous findings relating to motor imagery BCI performance (Seydell‐Greenwald, Greenberg, & Rauschecker, ).…”
Section: Discussionmentioning
confidence: 99%
“…The SMA has also been shown to be active during real‐time feedback (Zich et al, ). Marchesotti et al () confirmed the role of SMA during motor imagery tasks, but also pointed out the contribution of areas outside the sensorimotor cortex to the BCI task, in particular the posterior parietal cortex and insular cortices.…”
Section: Introductionmentioning
confidence: 90%
“…Marchesotti et al () detected a selective activation increase in the striatum during motor imagery with neurofeedback when comparing meta‐analytic activation maps of motor imagery with and without providing neurofeedback and Johnston, Boehm, Healy, Goebel, and Linden () had reported increased activation in the ventral striatum with progression in neurofeedback training for up‐regulating negative affect by providing neurofeedback from individual areas that showed increased activation in response to negative affective image. In congruence with these reported activation increases in the striatum during neurofeedback, several theoretical frameworks note that BCI control/neurofeedback rewards subjects for a certain mental operation or neural state, notably by underling the crucial involvement of operant/instrumental conditioning in neurofeedback (Fetz, ), by interpreting BCI control training as skill learning that is heavily dependent on plasticity in the basal ganglia (Birbaumer, Ruiz, & Sitaram, ) or by underlining the importance of feedback loops for biofeedback learning in general (Lacroix & Gowen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of motor areas in the sense of agency is theoretically supported by a computational model of agency, the comparator model (Frith, Blakemore, & Wolpert, 2000), which is based on a model for sensorimotor integration (Wolpert, Ghahramani, & Jordan, 1995) and describes agency as the result of a matching between predicted and actual sensory feedback of a planned motor action (Blakemore, Wolpert, & Frith, 2000;Frith et al, 2000). Further, brain regions related to BCI control not related to the comparator model have been identified in the basal ganglia, the anterior cingulate cortex and the left superior frontal gyrus (Marchesotti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%